Comparison of Serum Interleukin-6 (Il-6) Levels Between Patients With HELLP Syndrome Versus Normotensive Pregnant - Ganap, Eugenius Phyowai; Sofoewan, Sulchan; Siswosudarmo, Risanto (Sains Medika: Jurnal Kedokteran dan Kesehatan, 2018)
Background: Interleukin-6 (IL-6) has been known associated with oxidative stress and endothelial dysfunction, and also has important roles in pathogenesis of preeclampsia. Several studies have demonstrated that there was a significant increase of serum IL-6 levels in preeclamptic compared to normotensive pregnant women. However, study to evaluate serum IL-6 level in pregnant women with HELLP (hemolysis, elevated liver enzyme, and low platelet) syndrome is not well documented yet. This study aims to evaluate serum IL-6 levels between women with HELLP syndrome compared to normotensive pregnant.Methods: The research design was observational cross-sectional study. Samples were recruited consecutively using inclusion and exclusion criteria from emergency department and inpatient wards at Dr. Sardjito General Hospital, Yogyakarta, Indonesia. Serum IL-6 were collected from venous blood sample and measured by enzyme-linked immunoassay (ELISA) method. Independent-samples t-test or Mann-Whitney test was used to compare serum IL-6 values between women with HELLP syndrome and normotensive pregrnancy. A statistical measurement conducted using SPSS IBM Statistics 19® and considered significance when p<0,05.Results: There were 46 subjects, consisted of 23 women with HELLP syndrome and 23 women with normotensive pregnancy. Serum IL-6 level was a mean of 0,11±0,08 pg/mL and 0,15±0,20 pg/mL in women with HELLP syndrome compared to normotensive pregnancy respectively. There was no significant statistical difference between both groups (p=0,17).Conclusion:.The result of this study has shown that no significant difference of serum IL-6 level in HELLP syndrome women compared to normotensive pregnant women.